Aliran Permukaan, Erosi dan Hara Sedimen Akibat Tindakan Konservasi Tanah Vegetatif pada Kelapa Sawit - Zahrul Fuady; Halus Satriawan; Nanda Mayani (Faculty of Agriculture, Universitas Sebelas Maret, 2014)
Title : Runoff, Erosion and Nutrient Sediment due Vegetative Soil Conservation Applied on Oil Palm Plantation. Land cover crops play an important role in influencing erosion. Cover crops provide protection against the destruction of soil aggregates by rain and runoff. This research aims to study the effectiveness of vegetation as soil conservation in controlling erosion and runoff. This study was a field experiment on erosion plots measuring 10 m x 5 m were arranged in Split Plot design with replications as blocks, consists of a combination of two factors: the age of the oil palm and slope as the first factor, and vegetative soil conservation techniques as a second factor. The results showed the soil conservation techniques in oil palm cultivation can reduce the rate of surface runoff, soil erosion and nutrient loss. Soil conservation with upland rice planted with soybean sequence + strip Mucuna bracteata (T3) most effectively reduce runoff and prevent soil erosion and nutrient loss.